Declining responsiveness to influenza vaccination with progression of human pregnancy. Issue 31 (25th July 2018) - Schlaudecker, Elizabeth P.; Ambroggio, Lilliam; McNeal, Monica M.; Finkelman, Fred D.; Way, Sing Sing
Highlights: Reduced neutralizing antibody levels after influenza vaccination during pregnancy. Declining protective responses with immunization initiated later during pregnancy. Vaccine primed IgG1, IgG2, and IgG3 antibodies decline with pregnancy progression. Abstract: Background: Influenza immunization is universally recommended during pregnancy to protect mothers and their offspring. However, pregnancy-induced shifts in vaccine responsiveness remain poorly defined. Methods: Quantitative and qualitative shifts in the serological response to influenza vaccination were evaluated in healthy women throughout the course of pregnancy. Serum was obtained before and after vaccination among 71 pregnant and 67 non-pregnant women during the 2011–12 and 2012–13 influenza seasons. Serum hemagglutination inhibition (HAI) assay was used to investigate anti-influenza antibody responses by comparing pre-vaccine and post-vaccine geometric mean titers (GMTs) between groups for each antigen. IgG1, IgG2, IgG3, and IgG4 anti-influenza titers were also evaluated by enzyme-linked immunosorbent assay (ELISA). Pregnancy induced shifts in HAI titers and levels of each anti-influenza antibody isotype were evaluated using linear regression models. Results: Post-vaccine GMTs at day 28 were significantly reduced for women vaccinated during pregnancy for A/California (H1N1) in 2011 ( p = 0.027), A/Perth (H3N2) in 2011 ( p = 0.037), and B/Wisconsin in 2012 ( p = 0.039). Vaccine responses progressively declined with the initiation of vaccination later in pregnancy. Anti-H1N1 IgG1, IgG2, and IgG3 titers were reduced in pregnant women compared to non-pregnant controls, and these titers declined with pregnancy progression. The most striking differences were found for anti-H1N1 IgG1, where titers decreased by approximately 7% each week throughout pregnancy. Conclusions: HAI responses elicited by immunization were significantly reduced during pregnancy for three different influenza vaccine antigens. Anti-H1N1 IgG1 was significantly lower in pregnant women and decreased throughout the course of pregnancy. Waning serological responsiveness to influenza vaccination with the progression of human pregnancy has important translational implications for when immunization should be optimally administered during pregnancy.